Empirical Study of Emotional Intelligence Among Higher - Education Teachers and Role of Certifications on Emotional Intelligence Levels - Joshi, Meha; Bisht, Deepa (Prabandhan: Indian Journal of Management, 2019)
In this competitive world, education plays a very important role in the success of a child in each and every discipline. Teachers are the instrument on which the very foundation of education is based since the Vedic age. There are many studies which showed that emotional intelligence is one of the most important personal competencies of teachers, which is very important for teachers' effectiveness. Organizations in higher education are working on training and development programmes for raising the emotional intelligence level of the faculty members. Looking into the various studies undertaken related to the emotional intelligence of higher education teachers and their effectiveness in terms of students' overall development and academic achievement, the present study was undertaken. Descriptive survey method was employed, and the sample consisted of 100 teachers who belonged to the management and engineering fraternity. The findings of the study revealed that teachers possessed average overall emotional intelligence. It was also found that the level of emotional intelligence and its various factors were found to be significantly higher for the faculty members of higher education who were provided with the provision of development programmes for the faculty by the organizations as compared to the faculty members with no such provisions. Interpersonal management and intrapersonal management combined together were the major contributing factors to the emotional intelligence level of teachers.